Serial Procalcitonin Predicts Mortality in Severe Sepsis Patients: Results From the Multicenter Procalcitonin MOnitoring SEpsis (MOSES) Study. Issue 5 (May 2017) - Schuetz, Philipp; Birkhahn, Robert; Sherwin, Robert; Jones, Alan E.; Singer, Adam; Kline, Jeffrey A.; Runyon, Michael S.; Self, Wesley H.; Courtney, D. Mark; Nowak, Richard M.; Gaieski, David F.; Ebmeyer, Stefan; et al.
Abstract : Objectives: To prospectively validate that the inability to decrease procalcitonin levels by more than 80% between baseline and day 4 is associated with increased 28-day all-cause mortality in a large sepsis patient population recruited across the United States. Design: Blinded, prospective multicenter observational clinical trial following an Food and Drug Administration-approved protocol. Setting: Thirteen U.S.-based emergency departments and ICUs. Patients: Consecutive patients meeting criteria for severe sepsis or septic shock who were admitted to the ICU from the emergency department, other wards, or directly from out of hospital were included. Interventions: Procalcitonin was measured daily over the first 5 days. Measurements and Main Results: The primary analysis of interest was the relationship between a procalcitonin decrease of more than 80% from baseline to day 4 and 28-day mortality using Cox proportional hazards regression. Among 858 enrolled patients, 646 patients were alive and in the hospital on day 4 and included in the main intention-to-diagnose analysis. The 28-day all-cause mortality was two-fold higher when procalcitonin did not show a decrease of more than 80% from baseline to day 4 (20% vs 10%; p = 0.001). This was confirmed as an independent predictor in Cox regression analysis (hazard ratio, 1.97 [95% CI, 1.18–3.30; p < 0.009]) after adjusting for demographics, Acute Physiology and Chronic Health Evaluation II, ICU residence on day 4, sepsis syndrome severity, antibiotic administration time, and other relevant confounders. Conclusions: Results of this large, prospective multicenter U.S. study indicate that inability to decrease procalcitonin by more than 80% is a significant independent predictor of mortality and may aid in sepsis care. Abstract : Supplemental Digital Content is available in the text.